Calculate x in square root(2x-1)=3?

### 1 Answer | Add Yours

You need to raise to square both sides to eliminate the radical, such that:

`(sqrt(2x - 1))^2 = 3^2 => 2x - 1 = 9`

You need to isolate the term that contains `x` to one side, such that:

`2x = 9 + 1 => 2x = 10 => x = 10/2 => x = 5`

You need to test the value `x = 5` in equation, such that:

`sqrt(2*5 - 1) = 3 => sqrt(10 - 1) = 3 => sqrt 9 = 3 => 3 = 3`

**Hence, evaluating the solution to the given equation yields `x = 5.` **

### Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes